Transition from a pay-as-you-go to a fully-funded pension system: The case of differing individuals and intragenerational fairness - Johann K. Brunner (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1993)
In recent contributions to the theory of public pension systems it was argued that a Pareto-improving transition from an established unfunded pension system to a funded one is possible. This result is derived in an overlapping-generations model with identical individuals. In the present study an extended model, with differing individuals, of an intragenerationally fair unfunded pension scheme is introduced. Within this more realistic framework it is shown that, in general, a Pareto-improving transition to a funded system is not possible, because any instrument applied for the financing of pensions in the phase of transition involves intragenerational redistribution.
Keywords: 330